2013
DOI: 10.3103/s1067821213020089
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the question of complex processing of bauxites of the srednetimanskoe deposit

Abstract: 143From the moment the Bayer method appeared in alumina technology, the notion of the quality of the bauxite raw material has been a constant. The most basic and constantly accompanying impurity of the latter is silica, which almost completely dissolves dur ing the production process, transferring into sodium silicate. In turn, favorable conditions for the interac tion of sodium silicate with components of the alkalialuminate solution appear with the formation of low soluble sodium aluminum silicate hydrate (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Most combined pyro/hydrometallurgical treatments of bauxite residue use a pyrometallurgical step to first recover iron from bauxite residue and to subsequently concentrate the rare earths in an oxide slag (Liu et al, 2009b;Logomerac, 1979a;Logomerac, 1979b;Loginova et al, 2013). The efforts made to extract iron from bauxite residue have been described above.…”
Section: Recovery Of Rare Earths From Red Mudmentioning
confidence: 99%
See 1 more Smart Citation
“…Most combined pyro/hydrometallurgical treatments of bauxite residue use a pyrometallurgical step to first recover iron from bauxite residue and to subsequently concentrate the rare earths in an oxide slag (Liu et al, 2009b;Logomerac, 1979a;Logomerac, 1979b;Loginova et al, 2013). The efforts made to extract iron from bauxite residue have been described above.…”
Section: Recovery Of Rare Earths From Red Mudmentioning
confidence: 99%
“…During reductive smelting of bauxite residue, 98-99% of the scandium content reports to the slag phase (Tanutrov et al, 2013). Scandium has been recovered from slag obtained by smelting of Chinese bauxite residue, by leaching with 30% H 2 SO 4 , followed by solvent extraction with bis(2ethylhexyl)phosphoric acid in sec-octanol/kerosene diluent, and stripping with NaF solution from the loaded organic phase to obtain Na 3 ScF 6 (Xu and Li, 1996) The combined use of pyrometallurgical and hydrometallurgical methods for recovery of metal values of bauxite residue is called complex processing (Zazubin et al, 1967;Sargic and Logomerac, 1974;Loginova et al, 2013).…”
Section: Recovery Of Rare Earths From Red Mudmentioning
confidence: 99%
“…are then leached under certain conditions to produce iron oxides and hydroxides with a high specific surface area and magnetic properties [64,65]. However, the use of red mud obtained by this method as an adsorbent for arsenic removal without additional treatment has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in this country, about 20% of the generated fly ash being used in concrete production. Other areas of utilization include: land reclamation, ceramic industry, production of catalysts and We have conducted earlier research on the processing of aluminum raw materials [5,6] showed that the fusing aluminum containing minerals with alkali eliminates the need of autoclave or high-temperature processing. To explore the possibility of applying this method for the processing of fly ash studies have been conducted on the fusing of pre-desilicated fly ash with caustic alkali at different temperatures from 100…”
Section: Introductionmentioning
confidence: 99%